1996
DOI: 10.1029/96je00468
|View full text |Cite
|
Sign up to set email alerts
|

System design of a mission to detect Earth‐sized planets in the inner orbits of solar‐like stars

Abstract: A point design for a mission to detect Earth‐sized planets in the inner orbits of solar‐like stars is described. The observing technique is based upon continuously and simultaneously monitoring 5000 solar‐like stars for brightness changes that would be caused by planets transiting their star. Detection of periodic transits of the same amplitude and duration provides for a robust method of discovery. The instrument would consist of a 1‐m Schmidt telescope with an array of charge‐coupled devices (CCDs) filling t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…A compact system of six transiting planets (Kepler-11, Lissauer et al 2011), five of which were confirmed by their mutual gravitational interactions exhibited through transit timing variations (TTVs), has also been reported. These systems provide important data for understanding the dynamics, formation and evolution of planetary systems (Koch et al 1996;Agol et al 2005;Holman & Murray 2005;Fabrycky 2009;Ragozzine & Holman 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A compact system of six transiting planets (Kepler-11, Lissauer et al 2011), five of which were confirmed by their mutual gravitational interactions exhibited through transit timing variations (TTVs), has also been reported. These systems provide important data for understanding the dynamics, formation and evolution of planetary systems (Koch et al 1996;Agol et al 2005;Holman & Murray 2005;Fabrycky 2009;Ragozzine & Holman 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A network was organized to search for transit of extrasolar planets (the "TEP" network). Moreover, space missions have been proposed to conduct long and continuous observations of large samples of stars to exploit the method of transits (Koch et al 1996;Borucki et al 1997). One of the main programs of the satellite COROT, that will be launched in 2001, is to achieve this goal (Schneider et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Аналогичный американский проект Kepler [54] разработан на основе ранее предлагаемого проекта FRESIP [113], как составная часть программы NASA Discovery. Имея однометровую апертуру и поле зрения 12 • , предлагается непрерывно отслеживать около 80 000 звезд главной последовательности ярче 14 m , с фотометрической точностью 10 −5 .…”
Section: динамические методы обнаруженияunclassified